Addressing the issue of sexual orientation in the classroom – attitudes of Israeli education students. Issue 1 (2nd January 2019) - Glikman, Anya; Elkayam, Tal Shemer
Abstract: Lesbian, gay, bisexual and transgender (LGBT) pupils continue to experience alienation and opposition in the school environment. The current study explored the willingness of education students to address the issue of sexual orientation with K–12 pupils. Findings reveal that participants were willing to address the issue of sexual orientation at various levels within the K–12 system, to varying extents, and in different ways. Moreover, education students strongly believed that teachers should oppose and prevent homophobic behavior in school. Notwithstanding this general attitude, participants reported insufficient knowledge to provide the type of assistance needed by pupils negotiating the issue of sexual orientation. This gap between the willingness to act and lack of knowledge highlights the need to ensure that teachers adapt the already existing educational programs, and to develop new ways to create LGBT-inclusive education in their schools.